Zina dalam Perspektif Hukum Islam dan Kitab Undang Undang Hukum Pidana - Syamsul Huda (State Institute of Islamic Studies (IAIN) Palu, 2015)
This article discusses about adultery in Islamic law perspective and the book of law and criminal. By using the comparative analysis method found a difference between Islamic law and the book of law and criminal in terms define adultery as well as legal consequences. Sexual relations between young couples are not categorized as adultery in the book of law and criminal because they are not in a valid marriage bond. The book of law and criminal also does not ensnare adultery to Article 27 BW even though they are in a valid marriage bond. In addition, if the husband or wife of adultery gives permission to the partner to commit adultery, then Article 284 cannot ensnare them. While in Islamic law perspective, any sexual relations outside a valid marriage bond is categorized as adultery